2019
DOI: 10.1080/21691401.2019.1642206
|View full text |Cite
|
Sign up to set email alerts
|

Alkannin restrains oral squamous carcinoma cell growth, migration and invasion by regulating microRNA-9/RECK axis

Abstract: Alkannin (ALK) has anti-inflammatory and anti-tumour activities. We tried to probe the underlying functions of ALK in oral squamous carcinoma (OSCC) cells growth, migration and invasion. OSCC cells viability was investigated after treatment with ALK. Then, BrdU, flow cytometry, Western blot and Transwell assays were executed to appraise proliferation, apoptosis, migration and invasion in OSCC cells with ALK stimulation. The biological functions of miR-9 were explored after miR-9 mimic/inhibitor transfection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In this work, we discovered that alkannin restricted CSCC cell viability in a dose‐dependent manner and accelerated CSCC cell apoptosis. This result was similar to the description of Mao et al 23 In addition, Nika et al indicated that polarization of macrophages served as a key regulatory factor in CSCC 24 . Moreover, Marie et al proved that oncostatin M is involved in modulating cell proliferation, migration, and macrophage M1 polarization to promote CSCC development 25 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this work, we discovered that alkannin restricted CSCC cell viability in a dose‐dependent manner and accelerated CSCC cell apoptosis. This result was similar to the description of Mao et al 23 In addition, Nika et al indicated that polarization of macrophages served as a key regulatory factor in CSCC 24 . Moreover, Marie et al proved that oncostatin M is involved in modulating cell proliferation, migration, and macrophage M1 polarization to promote CSCC development 25 .…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies have shown that alkannin plays a central role in many cancers. Mao et al showed that alkannin hindered oral squamous carcinoma cell growth, migration, and invasion while expediting apoptosis by modulating the miR‐9/RECK axis 23 . In this work, we discovered that alkannin restricted CSCC cell viability in a dose‐dependent manner and accelerated CSCC cell apoptosis.…”
Section: Discussionmentioning
confidence: 55%
“…To reveal the fundamental role of alkannin in cellular activities, we ascertained the treatment time and R e t r a c t e d concentrations of alkannin which was evaluated by detecting cell viability. According to a previous reported treatment time, 24 we incubated PANC-1 cells with 0, 1, 3, 5, and 10 μM of alkannin for 12 hr. Results in Figure 1b suggested that the viability was significantly repressed by alkannin at concentrations of 3 (p < .05), 5 (p < .01), and 10 μM (p < .001).…”
Section: Alkannin Repressed Viability Proliferation Migration and Inv...mentioning
confidence: 99%
“…A previous study demonstrated the regulatory mechanism underlying the targeting of RECK by miR-21 in other cancers; this study revealed that the molecular mechanisms underlying the promotion of cell proliferation, viability, invasion, and apoptosis by miR-21 via its target gene, i.e., RECK, are common in Gejiu squamous cell lung carcinoma and other non-small cell lung carcinomas 14) . In contrast, RECK inhibits tumor cell proliferation, invasion, and angiogenesis in several cancers, including OSCC [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%